Isolation and Characterisation of Compounds from ‘Naga Buana’ (Phyllanthus Pulcher) and ‘Similit Matinggi’ (Casearia Capitellata) and Their Cytotoxic Effects on Cancer Cell Lines - Bagalkotkar, Gururaj (2009)
Phyllanthus pulcher from the family of Euphorbiaceae is used as a traditional medicine in Malaysia to treat stomachache and ulceration. Casearia species from the family of Flacourtiaceae are traditionally used as an antiseptic, cicatrizant and topical anesthetic agent. In a preliminary cytotoxic screening, P. pulcher and C. capitellata extracts were found to display remarkable activities against various in vitro tumour cell lines. On the basis of the screening results and literature review of the plants, P. pulcher and C. capitellata were selected for phytochemical investigations to identify compounds with cytotoxic activities. The investigations of the active dichloromethane extract of aerial parts from P. pulcher by a combination of different chromatographic techniques led to the isolation of three new natural products, bis(6-methylheptyl)phthalate (190), phyllanthal-A (192) and 3,4- dihydroxy-5-methoxy-3’,4’,5’-trihydroxyoxepino-chromene-2-one (196) and five other known compounds including stigmast-5-en-3-ol-oleate (189), diisobutyl adipate (195), β- sitosterol (193), 7-tridecanone (194) and β-sitosteryl-β-D-glucopyranoside (191). The isolation of stigmast-5en-3ol-oleate (189) is the first report from the genus Phyllanthus. All isolated compounds were tested for their cytotoxic activities against three human tumour cell lines: MCF-7 (breast), DU-145 (prostate) and H460 (lung). Compounds, 189, 190, 191 and 192 were found to exhibit significant antitumour activity against MCF-7 cells with the IC50 values of 17.6, 69.2, 54.1 and 47.7 μM, respectively. Among all the isolated compounds from P. pulcher aerial parts only the phyllanthal-A (192) exhibited cytotoxic activity against DU-145 cells with the IC50 value of 20.5 μM. Whereas all the isolated compounds from P. pulcher aerial parts failed to exhibit cytotoxic effect against H460 cells even at the highest concentration of 100 μM. Investigation on the active dichloromethane extract of P. pulcher roots resulted in the isolation of two new compounds, 12(13)-dehydro-3α-acetoxyolean-28-oic acid (199) and lupanol acetate (200) and three other known compounds including 3α-acetoxy-25- hydroxyolean-12-en-28-oic acid (197), glochidone (198) and glochidonol (201). 3α- acetoxy-25-hydroxyolean-12-en-28-oic acid (197) which was isolated for the first time in this genus showed cytotoxic activity against MCF-7 and DU-145 cell lines. Whereas 201 exhibited potent antitumour activity against all the tested cell lines with the IC50 values ranging 17.0 - 30.0 μM. Among all the isolated compounds from P. pulcher only the 201 exhibited antitumour activity against H460 cells with the IC50 value of 21.7 μM. Investigation on the bioactive phytochemicals of C. capitellata stem bark extracts yielded 7α-acetoxy-hop-12(13)-en-11-one (202), 5-methoxy-7-hydroxycoumarin (203), 5- methoxy-7-β-D-glucopyranosylcoumarin (204), 5,7-dimethoxycoumarin (205), casearine-A (206) and casearine-B (207). The isolation of 206 and 207 has never been reported from natural products before, whereas the isolation of 202, 203, 204, and 205 is the first report from this genus. Among all the isolated compounds, 206 and 207 exhibited significant antitumour activity against MCF-7 and DU-145 cell lines with the IC50 values ranging 5.0-14.0 μM. 206 and 207 also exhibited cytotoxic activity against H460 cells with the IC50 values of 77.0 and 56.3 μM, respectively. The structures of all isolated compounds were elucidated with the help of chemical and modern spectroscopic techniques (UV, IR, MS, 1H NMR, 13C NMR, DEPT, COSY, HSQC, and HMBC). In conclusion, some of these natural products, especially 189, 192, 201, 206, and 207, are potential lead molecules for future antitumour studies to discover potential clinical candidates.